2012
DOI: 10.1038/modpathol.2011.145
|View full text |Cite
|
Sign up to set email alerts
|

Loss of DLC1 is an independent prognostic factor in patients with oral squamous cell carcinoma

Abstract: Deleted in liver cancer (DLC1), a Rho GTPase-activating protein, was observed to be differentially expressed in oral squamous cell carcinoma in comparison with normal tissues using tissue proteomics. In the current study, we investigated the clinical significance of loss of DLC1 expression in different stages of development of oral squamous cell carcinoma to determine its potential as a biomarker for oral dysplasia and prognosis of oral squamous cell carcinoma. Immunohistochemical analysis of DLC1 expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This result is consistent with a previous report in lung cancer that the degree of DLC1 methylation was inversely correlated with the extent of disease (45). A recent report also identified low DLC1 expression as a poor prognostic factor in oral squamous cell cancer (46). The results suggest DLC1 inactivation contributes to cancer progression, probably via the combined effects of its RhoGAP-dependent and RhoGAP-independent activities.…”
Section: Discussionmentioning
confidence: 97%
“…This result is consistent with a previous report in lung cancer that the degree of DLC1 methylation was inversely correlated with the extent of disease (45). A recent report also identified low DLC1 expression as a poor prognostic factor in oral squamous cell cancer (46). The results suggest DLC1 inactivation contributes to cancer progression, probably via the combined effects of its RhoGAP-dependent and RhoGAP-independent activities.…”
Section: Discussionmentioning
confidence: 97%
“…To determine a suitable cutoff point for the proportion of tumour cells with recognised staining alteration and dichotomising the level of immunohistochemical staining into either high or low expression groups, we used a receiver operating characteristic (ROC) curve according to the previous report ( Tripathi et al , 2012 ) with modifications. The values of the proportions of tumour cells with recognised staining alteration as a continuous variable and survival (alive or dead at the median follow-up time) as a binary variable were subjected to ROC analysis.…”
Section: Methodsmentioning
confidence: 99%
“…10 DLC1 was mapped to chromosome 8p21.3-22, a region frequently deleted in many solid tumors, including liver cancer, but has later also been found to be silenced by other, mainly epigenetic, mechanisms. [10][11][12] Since its initial discovery, several studies have reported DLC1 downregulation in a number of malignancies including breast, renal, lung, nasopharyngeal, esophageal, cervical, prostate, colorectal, oral squamous cell, and gastric carcinomas, as well as in multiple myelomas and lymphomas, [13][14][15][16][17][18][19][20][21][22][23] and these studies together with recent in vitro and in vivo studies have confirmed the role of DLC1 as a bona fide tumor suppressor. [24][25][26] In addition to containing a RhoGAP domain, responsible for catalyzing the hydrolysis of GTP bound to RhoA, RhoB, RhoC, and Cdc42, DLC1 also contains a steroidogenic acute regulatoryrelated lipid transfer domain, a sterile alpha motif domain, and a focal adhesion-targeting (FAT) domain.…”
mentioning
confidence: 93%